1991
DOI: 10.1901/jaba.1991.24-251
|View full text |Cite
|
Sign up to set email alerts
|

Functional Communication Training to Reduce Challenging Behavior: Maintenance and Application in New Settings

Abstract: We evaluated the initial effectiveness, maintenance, and transferability of the results of functional communication training as an intervention for the challenging behaviors exhibited by 3 students. Assessment indicated that escape from academic demands was involved in the maintenance of the challenging behaviors. Social attention was also implicated as controlling the behavior of 1 student. The intervention involved teaching alternative assistance-seeking and attention-getting phrases to the students in an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
193
1
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(213 citation statements)
references
References 20 publications
18
193
1
1
Order By: Relevance
“…First, the procedures described in the current investigation are limited in that the reinforcers that maintained appropriate behavior (e.g., compliance, requests for attention) were not empirically determined. However, the functional equivalence of problem behavior and appropriate communicative behavior has been demonstrated repeatedly in the behavior-analytic literature (Durand & Carr, 1991Northup et al, 1991). We are currently evaluating procedures to identify reinforcers for appropriate communicative behavior when problem behavior is not amenable to standard functional analysis procedures.…”
Section: Discussionmentioning
confidence: 99%
“…First, the procedures described in the current investigation are limited in that the reinforcers that maintained appropriate behavior (e.g., compliance, requests for attention) were not empirically determined. However, the functional equivalence of problem behavior and appropriate communicative behavior has been demonstrated repeatedly in the behavior-analytic literature (Durand & Carr, 1991Northup et al, 1991). We are currently evaluating procedures to identify reinforcers for appropriate communicative behavior when problem behavior is not amenable to standard functional analysis procedures.…”
Section: Discussionmentioning
confidence: 99%
“…One such early intervention strategy could be to actively promote early communicative behaviours (e.g., signing or verbal mands) in the children's repertoires at a very early stage (Carr & Durand, 1985;Durand & Carr, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of sophisticated improvements to both the behavioural analysis and treatment of self-injury in individuals with autism and/or developmental disabilities have occurred (Carr & Durand, 1985;Durand & Carr, 1991;Iwata et al, 1994;Murphy et al, 1993;Wacker et al, 1990). Studies have shown that SIB can be maintained by environmental consequences such as the contingent removal of demands, the contingent provision of attention and/or tangible items such as toys and by automatically produced sensory consequences (Carr, 1977).…”
mentioning
confidence: 99%
“…FCT has been shown to lead to rapid, durable, and generalized reductions in problem behavior without the occurrence of an extinction burst (Durand & Carr, 1991, 1992Sprague & Horner, 1992). The success of FCT has generally been attributed to the notion of functional equivalence (Carr & Durand, 1985a) in which the strengthening (through FCT) of a socially desirable response leads to the weakening or elimination of problem behavior responses having the same function.…”
Section: Functional Communication Training (Fct)mentioning
confidence: 99%